Investigation on mechanical behaviors of shale cap rock for geological energy storage by linking macroscopic to mesoscopic failures. (June 2020) - Liu, Yang; Ma, Tianshou; Wu, Hao; Chen, Ping
Highlights: l A numerical model is established to simulate the mechanical behaviors of shale cap rock by linking macroscopic to mesoscopic failures. l The deformation, strength features, progressive failure process and corresponding AE response are obtained. l The connections between macro- and meso‑failure are observed and discussed. l A method for determining the minimum hydraulic fracturing pressure for both intact caprocks and caprocks with pre-existing fractures is introduced. Abstract: Geological energy storage using subsurface porous rock is a feasible alternative that could satisfy the needs of future large-scale seasonal energy storage, where the petrophysical and mechanical properties of cap rock is vital to ensure safe and sustainable storage of energy. Shale rock is a typical cap rock for geological storage, but its failure behaviors have not been fully understood due to its severe heterogeneity and anisotropy. Numerical simulation methods have been widely acknowledged as an accurate and effective approach to investigate the mechanical and failure behaviors of different materials. For this purpose, this paper developed a numerical model to simulate the failure process of shale specimen when subjected to triaxial compression stresses. The deformation and strength features, progressive failure processes and corresponding acoustic emission (AE) response are obtained by numerical simulation. The performance of the numerical model is validated by experimental data. Simulation results suggest that the failure events which are accompanied by forming micro-fissures are randomly distributed on the specimen at the initial fracture stage. The failure patterns of shale can be summarized into three types, including shear failure, slip failure and splitting failure. The local fractures resulting from the growth of micro-cracks are the sources of shear failure. But high confining pressure has an inhibitory effect on the extension of parts of macroscopic fractures and may induce the contact between fracture surfaces to be rebuilt. While slip failure is caused by the structural surface destruction and the failure plane follows an irregular path that jumps between the bedding plane and the matrix. The propagation of micro-cracks parallel to the bedding plane is the governing factor of tensile failure. That means numerical modeling can be able to reproduce the triaxial test results to a large extent and reflect the rock failure process in detail, and it can help us to understand the macro- and meso‑properties of cap rock for geological energy storage.